2010
DOI: 10.1002/jmri.22081
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cirrhosis with intravoxel incoherent motion diffusion MRI and dynamic contrast‐enhanced MRI alone and in combination: Preliminary experience

Abstract: Purpose To report our preliminary experience with the use of intravoxel incoherent motion (IVIM) diffusion-weighted magnetic resonance imaging (DW-MRI) and dynamic contrast-enhanced (DCE)-MRI alone and in combination for the diagnosis of liver cirrhosis. Materials and Methods Thirty subjects (16 with noncirrhotic liver, 14 with cirrhosis) were prospectively assessed with IVIM DW-MRI (n = 27) and DCE-MRI (n = 20). IVIM parameters included perfusion fraction (PF), pseudodiffusion coefficient (D*), true diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
376
7
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 342 publications
(412 citation statements)
references
References 52 publications
28
376
7
1
Order By: Relevance
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Various fitting algorithms have been used to determine IVIM parameters, including asymptotic fitting (9)(10)(11)(12)(19)(20)(21)24,41,45,46,48,51,53), nonlinear least square (usually Levenberg-Marquardt) fitting (23,42,47,52,54,55), and Bayesian fitting (15,22,40,43,50). Current review cannot draw conclusion which one is better than others, nor can the mean values be compared (Figure 8).…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…Guiu et al (9) reported that Dslow and Dfast were significantly lower in steatotic compared with nonsteatotic livers; however, PF was significantly higher in steatotic compared with nonsteatotic livers. In another study, Patel et al (12) reported that the value of Dslow, PF and Dfast in liver cirrhosis were lower than non-cirrhosis liver; however, no further grading was performed within their liver cirrhosis subjects as only three patients had histopathology data. In a rat model of diethylnitrosamineinduced liver fibrosis, Zhang et al (57) reported that PF values decreased significantly with the increasing fibrosis level; but Dslow was poorly correlated with fibrosis level.…”
Section: Ivim For Liver Fibrosis Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). Since a simultaneous fit of all these parameters could be difficult, given the high dispersion and the limited sampling of DwI signals at low b value (bb150 s/mm 2 ) [23,24], a twostep fitting procedure was adopted, as described in other papers [25,26].…”
Section: Dwi Quantitative Analysismentioning
confidence: 99%
“…A further indispensable step is to examine the reproducibility and the repeatability of the method. Such measurements in the brain and abdominal imaging are scarce, mostly due to the demand for sufficiently high-quality images acquisition [18]. The next formal action is to test the sensitivity of the method for quantifying the fluctuation of capillary blood flow during induced vasoconstriction or vasodilatation [19,20].…”
mentioning
confidence: 99%